COMPARISON OF COLLECTION DEVELOPMENT IN UK UNIVERSITY LIBRARIES AND INDIAN INSTITUTE OF TECHNOLOGY LIBRARIES - Adzkiyah Mubarokah; Sri Rohyanti Zulaikha (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
This article discusses the development of existing collections in college libraries, using a comparison of case studies in the UK Library and the Indian East Institute of Technology Library. The purpose of this study is to find out the process of developing collections in libraries. The method used is a study of literature such as jurnals and books as well as other reading materials that contain the development of library collections. Research is reviewed based on theories related to collection development, namely the principle of collection development adopted by the National Library of the Republic of Indonesia. The results obtained are first in the UK library to develop collections by emphasizing content development by involving several collection development selection processes which are usually procured through purchase and also Cooperation with nss institutions or National Student Surveys. Secondly from the library of the Eastern Institute of Technology of India carried out collection development, the library is located in two locations named after IIT Guwahati library and IIT Patna.Aspects of collection development, namely selection, acquisition, finance and management of collections, play an important role in the development of collections to serve their users. The resources acquired in the selected IIT are identified by the pricing option and review the license of the electronic resource but with other different modes of acquisition. there are many shortcomings, especially in the network of connections from outside so that the system of developing library material collections becomes less than optimalKeywords: development; collections ; library